ANALYSIS OF FACTORS AFFECTING AVOCADO FARMING INCOME IN BUKIT SUBDISTRICT, BENER MERIAH REGENCY - Haulina Sari; Cut Rozana Sari; Wahyu Isnanda Nasution (Jurnal Mahasiswa Agribisnis, 2026)
This study aims to analyze avocado farming income and identify the factors that influence it in Bukit Subdistrict, Bener Meriah Regency. Although Bukit Subdistrict is an avocado production center, harvest price fluctuations often cause farmers' incomes to be unstable. The study employs a quantitative approach using a survey method. The research sample consists of 30 avocado farmers in Bale Atu and Bale Redelong villages, selected through purposive sampling. Primary data was collected through interviews, while secondary data was obtained from relevant agencies, books, and journals. Data analysis was conducted using multiple linear regression. The results showed that the average income of avocado farmers was Rp 2,194,140 per production cycle, with an average total cost of Rp 2,038,094, resulting in an average farmer income of Rp 156,045.32. Simultaneously, the variables of land area, capital, and production significantly influence avocado farmers' income with an Adjusted R² value of 0.634. However, partially, land area does not significantly influence income, capital significantly influences income with a negative coefficient, while production significantly and positively influences income. These findings indicate that improving productivity and capital use efficiency are important strategies for increasing avocado farmers' income in Bukit Subdistrict.